2017
DOI: 10.1007/s00467-017-3758-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo weekly and biweekly darbepoetin alfa dosing in pediatric patients with chronic kidney disease

Abstract: Darbepoetin alfa can be safely administered either QW or Q2W to ESA-naïve pediatric patients with CKD-related anemia to achieve Hb targets of 10.0-12.0 g/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Randomization was low risk in one trial [ 28 ]. The other five were unclear risk, with missing details on randomization or concealment [ 29 , 30 ]. Blinding was unclear risk in one study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Randomization was low risk in one trial [ 28 ]. The other five were unclear risk, with missing details on randomization or concealment [ 29 , 30 ]. Blinding was unclear risk in one study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] conducted an open-label non-inferiority trial in 124 children randomized (1:2) to ongoing rHuEPO therapy or DA, with results demonstrating an equivalent mean change in Hb over 28 weeks. The same team performed a prospective, multicentre double-blind randomized controlled trial of 114 ESA-naïve children comparing weekly versus fortnightly titrated dosing [ 29 ]. This showed that the mean time to target Hb of 10–12 g/dL was equivalent (22 days and 24 days, respectively), although a greater proportion of patients on weekly dosing reached the target Hb at 24 weeks (98% versus 84%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ESAs may pose logistical challenges given their expense, need for insurance approval in addition to the need for frequent injections, which often make them an unattractive option to pediatric patients and their caregivers. ESAs also require frequent hemoglobin monitoring given the risk of polycythemia and may also be associated with worsening hypertension ( 89 ). More extensive studies are needed to determine the optimal dosing and safety of ESA for the treatment of pediatric PTA.…”
Section: Discussionmentioning
confidence: 99%